SWEAR WORDS IN THE MOVIE MIDNIGHT RUN - , R.A. KHOIRI LULU NAJMI, Drs. Tofan Dwi Hardjanto, MA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Swear words are often heard and spoken spontaneously. They are usually intended to express when angry, depressed, joking, hateful, frustrated, disappointed, surprised, or excited. This graduating paper examines swear words found in the American movie Midnight Run. The data used in this research were dialogues containing swear words. The results show that 193 swear words were found in the movie. 10 swear words (5.2%) belong to anatomical terms, 19 (9.9%) to animal terms, 89 (46.2%) to copulative terms, 29 (15.1%) to excretory terms, 9 (4.5%) to imbecilic terms, 16 (8.3%) to religious terms, and 21 (10.8%) to spirits or death terms. This shows that copulative terms are the most commonly used for swearing. This research also found 7 functions used in this movie. The most commonly used function is for expressing anger 106 (55%), expressing amazement 36 (18.7%), expressing annoyance 20 (10.3%), expressing intimacy 14 (7.2%), expressing insult 13 (6.7%), expressing disappointment 3 (1.6%), and expressing regret 1 (0.5%).